Mammalian antibiotic peptides - Síma, P; Trebichavský, I; Sigler, K (Folia microbiologica, 2003)
The increasing development of bacterial resistance to traditional antibiotics has reached alarming levels, thus creating a strong need to develop new antimicrobial agents. These new antibiotics should possess novel mechanisms of action and different cellular targets compared with existing antimicrobials. Recent discoveries and isolations of so-called animal antibiotics, mostly small cationic peptides, which represent a potent branch of natural immunity, offered the possibility to acquire new and effective antibiotics of this provenance. To this date, more than 500 antibiotic peptides have been distinguished and defined. Their antimicrobial properties present new opportunities for their use as antibiotics or for construction of their more effective derivatives, but much research is still required to pave the way to their practical use. This is a survey of substances forming an armamentarium of natural immunity of mammals.
Keywords: eozinofily; přirozená imunita; Bacterial Infections; Eosinophils; antibakteriální látky; Blood Platelets; Bacteria; Immunity, Innate; neutrofily; bakteriální infekce; trombocyty; Animals; lidé; Anti-Bacterial Agents; Humans; zvířata; makrofágy; Peptides; Neutrophils; peptidy; Macrophages